The Influence of Sources of Information and the Role of Parents on Vaginal Discharge Prevention Behavior in Adolescent Girls - Rini, Ageng Septa (PT Inovasi Pratama Internasional, 2023)
Vaginal discharge can be a manifestation of a reproductive organ disease, namely cervical cancer. Research on reproductive health shows that 75% of women in the world will experience vaginal discharge at least once in their lifetime and 45% of them will experience vaginal discharge 2 or more times. This research aims to determine the direct and indirect influence as well as the magnitude of information sources and the role of parents on vaginal discharge prevention behavior among young women at SMA 38 Jakarta in 2023. Cross-sectional research design using a quantitative approach. The instrument used is a closed questionnaire. This research uses saturated sampling. Sample of 90 Young Women. The data analysis used is Structural Equational Model (SEM) using Smart PLS 2.0. The results of the study showed that the behavioral variable for preventing vaginal discharge in young women at SMA 38 Jakarta was directly influenced by the source of information (29.24%) and the role of parents (31.4%), while other factors not studied influenced the behavioral variable by 2.74%. It is recommended that young women get clear sources information and the role of parents and schools should provide information about vaginal discharge prevention behavior.